Pengelolaan Pembiayaan Pendidikan pada Jenjang Pendidikan Dasar (Studi Deskriptif Penggunaan Dana BOS Sekolah) - Revan Dwi Erlangga; Suryadi Suryadi; Fitroh Hayati (Journal on Education, 2024)
Bantuan Oprasional Sekolah (BOS) are one of the school's financial sources for carrying out educational activities at school. Schools are obliged to plan the allocation of funds carefully and calculatingly, as well as monitor the use of funds for operational and capital costs, as well as provide administrative and physical (material) evidence of how funds are used. However, unfortunately there are still many schools that are still indifferent to managing school finances, especially BOS funds. For this reason, this research aims to determine the management of education financing, in this case BOS funds, as a guide for other institutions in managing BOS funding in accordance with established regulations. The method used in this research uses a qualitative descriptive method with data collection using observation, interview and documentation techniques. The results of this research are: a) planning a budget by identifying goals, determining priorities, describing goals into measurable operational performance, analyzing alternatives for achieving goals with cost-effectiveness analysis, making recommendations for alternative approaches to achieving targets. b) budget realization by making real expenditures according to needs and physical evidence. c) carry out budget supervision and control, supervision carried out by certain parties within the school whose official function is to carry out supervision such as the principal and treasurer of the BOS, as well as the education office and the BPK as external supervisors of BOS finances in the school.